A highly durable p-LaFeO3/n-Fe2O3 photocell for effective water splitting under visible light1. Issue 17 (28th February 2015) - Yu, Qing; Meng, Xianguang; Wang, Tao; Li, Peng; Liu, Lequan; Chang, Kun; Liu, Guigao; Ye, Jinhua
<x xml:space="preserve">Abstract</x> A new p-type photocathode LaFeO3 was successfully fabricated, and a stable (120 h) and effective water splitting (H2: 11.5 μmol h−1, O2: 5.7 μmol h−1) was realized via construction of a p-LaFeO3/n-Fe2O3 photocell.